Prevalence of diabetes and pre-diabetes in Bangladesh: a systematic review and meta-analysis - Baki Billah; Sohail Akhtar; Jamal Abdul Nasir; Aqsa Sarwar; Nida Nasr; Amara Javed; Rizwana Majeed; Muhammad Abdus Salam (BMJ Open)
Objective The purpose of this paper is to perform a systematic review and meta-analysis in order to summarise the prevalence of diabetes and pre-diabetes and their associated risk factors in Bangladesh.Design Systematic review and meta-analysis.Participants General population of Bangladesh.Data sources PubMed, Medline, Embase, Bangladesh Journals Online, Science Direct, Scopus, Cochrane Library and Web of Science were used to search for studies, published between 1st of January 1995 and 31st of August 2019, on the prevalence of diabetes and pre-diabetes and their associated risk factors in Bangladesh. Only articles published in the English language articles were considered. Two authors independently selected studies. The quality of the articles was also assessed.Results Out of 996 potentially relevant studies, 26 population-based studies, which together involved a total of 80 775 individuals, were included in the meta-analysis. The pooled prevalence of diabetes in the general population was 7.8% (95% CI: 6.4–9.3). In a sample of 56 452 individuals, the pooled prevalence of pre-diabetes was 10.1% (95% CI: 6.7–14.0; 17 studies). The univariable meta-regression analyses showed that the prevalence of diabetes is associated with the factors: the year of study, age of patients and presence of hypertension. The prevalence of diabetes was significantly higher in urban areas compared with rural areas, while there was no significant gender difference.Conclusions This meta-analysis suggests a relatively high prevalence of pre-diabetes and diabetes in Bangladesh, with a significant difference between rural and urban areas. The main factors of diabetes include urbanisation, increasing age, hypertension and time period. Further research is needed to identify strategies for early detecting, prevention and treatment of people with diabetes in the population.PROSPERO registration number CRD42019148205.